Interferon (IFN)-gamma (γ) inducible protein 10 (IP-10) in the diagnosis of latent and active tuberculosis in Bacille Calmette Guerin (BCG)-vaccinated pediatric population. - Magdalena Druszczynska; Michał Seweryn; Sebastian Wawrocki; Anna Pankowska; Anastasiia Kulbachko; Magdalena Jurczak; Magdalena Kowalewska-Pietrzak (PLoS ONE)
Background Accurate diagnosis of tuberculosis (TB) in children continues to be challenging, primarily due to the low bacterial load characteristic of the disease and the obstacles in collecting sputum samples. Furthermore, detecting cases of latent Mycobacterium tuberculosis (M.tb) infection (LTBI) that have a high risk of progressing to active TB disease remains a significant diagnostic hurdle. Objective The study explored the utility of interferon-gamma (IFN-γ) inducible protein 10 (IP-10) for diagnosing latent and active M.tb infections among children vaccinated with the Bacille Calmette-Guerin (BCG) vaccine. The research specifically assessed IP-10 levels in serum, urine, and QuantiFERON-TB Gold Plus (QFT) cultures stimulated with M.tb antigens to determine if IP-10 could be a useful diagnostic marker for pediatric tuberculosis, either alongside or as an alternative to IFN-γ. Results Both urine and QFT cultures stimulated with M.tb antigens showed significantly higher IP-10 levels in individuals with active TB or latent TB infection (LTBI) when compared to those uninfected by M.tb but with nonmycobacterial pneumonia (NMP) and healthy controls (HC). Similarly, IFN-γ levels in M.tb-stimulated QFT cultures were significantly higher in the TB and LTBI groups compared to the NMP and HC groups. Notably, the study found a significant difference in IFN-γ levels between the TB and LTBI groups in the QFT cultures, a distinction not observed for IP-10 concentrations. Serum levels of IP-10 and IFN-γ did not significantly vary across the study cohorts. Conclusions IP-10 might be a viable alternative biomarker to IFN-γ for identifying M.tb infection in BCG-vaccinated children, although it cannot distinguish between latent and active TB cases. This highlights the potential of IP-10 in improving TB diagnosis among children, addressing the challenges posed by the paucibacillary nature of pediatric TB, but also underscores the need for further research to refine diagnostic approaches for distinguishing between latent and active TB infections.